In Situ Localization of Enzyme Activity in Live Cells by a Molecular Probe Releasing a Precipitating Fluorochrome. (15th August 2017) - Liu, Hong‐Wen; Li, Ke; Hu, Xiao‐Xiao; Zhu, Longmin; Rong, Qiming; Liu, Yongchao; Zhang, Xiao‐Bing; Hasserodt, Jens; Qu, Feng‐Li; Tan, Weihong
Abstract: Current enzyme‐responsive, fluorogenic probes fail to provide in situ information because the released fluorophores tend to diffuse away from the reaction sites. The problem of diffusive signal dilution can be addressed by designing a probe that upon enzyme conversion releases a fluorophore that precipitates. An excited‐state intramolecular proton transfer (ESIPT)‐based solid‐state fluorophore HTPQ was developed that is strictly insoluble in water and emits intense fluorescence in the solid state, with λ ex/em =410/550 nm, thus making it far better suited to use with a commercial confocal microscope. HTPQ was further utilized in the design of an enzyme‐responsive, fluorogenic probe (HTPQA), targeting alkaline phosphatase (ALP) as a model enzyme. HTPQA makes possible diffusion‐resistant in situ detection of endogenous ALP in live cells. It was also employed in the visualizing of different levels of ALP in osteosarcoma cells and tissue, thus demonstrating its interest for the diagnosis of this type of cancer.